LB11. Rapid Rise in Decreased Susceptibility to Azithromycin among Shigella Isolates in the United States: A Look at National Surveillance Data, 2011–2017. (26th November 2018) - Friedman, Cindy; Plumb, Ian; Reynolds, Jared; Chen, Jessica; Tagg, Kaitlin; Caidi, Hayat; Watkins, Louise Francois; Karp, Beth
Abstract: Background: Shigella spp. cause ~500, 000 illnesses in the United States annually. Antibiotics are recommended for immunocompromised patients and shorten the duration of illness, thus limiting spread. First-line treatments include ciprofloxacin (CIP) and azithromycin (AZM). CIP resistance is a growing problem in the United States; decreased susceptibility to AZM (DSA) has been reported globally, particularly among men who have sex with men (MSM). We reviewed National Antimicrobial Resistance Monitoring System (NARMS) data to determine DSA trends among Shigella isolates in the United States. Methods: Health departments nationwide forward every 20th Shigella isolate to CDC NARMS for antimicrobial susceptibility testing using broth microdilution. We defined CIP resistance using CLSI clinical breakpoints and DSA using epidemiological cutoff values where available. We performed whole genome sequencing on isolates from 2016 and screened the sequences for resistance determinants using ResFinder 3.0. Results: To date, we have tested 3, 044 Shigella isolates collected during 2011–2017. Overall, 264 isolates (9%) had DSA, increasing from 3% in 2011 to 23% in 2017; 41 (16%) were also CIP resistant. The odds of DSA increased by 1.5 (95% confidence interval [CI] 1.4–1.6) annually. DSA was more common among adult males (OR 21.2, CI 14.9–30.3), in isolates from the West census region (OR 2.4, CI 1.8–3.2), and in S. flexneri (OR 8.2, CI 6.3–10.7). Of 543 sequenced isolates, 52 (10%) had DSA; of these, 31 (60%) contained both mph(A ) and erm(B ) genes, 17 (33%) contained mph(A ) only, and 4 (8%) had no identified macrolide-resistance mechanism. Conclusions: In 2017, nearly 1 in 4 Shigella isolates tested had DSA, a 7-fold increase since 2011. This rapid rise in DSA parallels that seen in other countries, where resistance to other clinically relevant drugs is high and macrolides are no longer useful as empiric treatment. The increased risk of DSA in adult males is consistent with previous reports of DSA Shigella in MSM. The resistance genes observed are typically plasmid-mediated and can be transferred to other bacteria. Public health strategies to mitigate the spread of resistant Shigella should include antibiotic stewardship and novel approaches for sexually transmitted infection prevention in MSM. Disclosures: All authors: No reported disclosures.